2011
DOI: 10.3928/15428877-20110426-01
|View full text |Cite
|
Sign up to set email alerts
|

Use of Amniotic Membrane Graft in Glaucoma Shunt Surgery

Abstract: Amniotic membrane graft offers good tectonic support and allows direct visualization of the underlying tube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 30 publications
0
30
1
Order By: Relevance
“…Similar to AM, cryopreserved UCP also exerts therapeutic actions [18]. It is easier to handle [19] and has already been successfully used for the glaucoma shunt tubes covering [20] and conjunctival surface reconstruction [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Similar to AM, cryopreserved UCP also exerts therapeutic actions [18]. It is easier to handle [19] and has already been successfully used for the glaucoma shunt tubes covering [20] and conjunctival surface reconstruction [19]. …”
Section: Introductionmentioning
confidence: 99%
“…We have gathered preliminary data supporting the feasibility of using anterior segment optic coherence tomography (OCT) to detect the presence of AM and the evidence of host cell integration into the AM after being transplanted in the subconjunctival space to cover the glaucoma shunt tube. Our results showed that implanted AM maintained its thickness over a period of 12 months (Anand et al, 2011).…”
Section: Potential Advantages Of Ammentioning
confidence: 49%
“…The risk of infection [1, 2] and progressive exposure dictates prompt surgical intervention [3]. Different materials, including buccal mucosa [3], pericardium [4], human sclera [5], dura [6], and cornea [7], have been used to prevent exposure but none with universal success. In addition, there are several disadvantages particular to each material.…”
Section: Introductionmentioning
confidence: 99%